2019
DOI: 10.1111/apa.14684
|View full text |Cite
|
Sign up to set email alerts
|

Fasting insulin resistance affects the prevalence of metabolically healthy obesity in Brazilian adolescents

Abstract: Aim We aimed to assess the influence of fasting insulin resistance on metabolically healthy obesity (MHO) prevalence in adolescents and to identify associated factors. Methods This retrospective, registry‐based, cross‐sectional study included 418 (51.9% girls) 10‐ to 18‐year‐old adolescents with obesity from a tertiary outpatient clinic in Sao Paulo, Brazil, between 2009 and 2013. The prevalence of MHO was estimated according to two definitions: (i) no cardiometabolic risk factors (CMRF) by the International D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Indeed, the area under the ROC curve for the HOMA criterion indicates that the probability of diagnosing a patient more accurately than a randomly chosen healthy child is just 85.4%, whereas for the IDF criteria this is only 65.9%. Consequently, when we considered the four diagnostic criteria, the proportion of children classified with MHO was similar to some studies carried out in adults (32), and the children classified with MHO had clinical and analytical variables similar to those who theoretically have MUO. No statistically significant differences were found in any of the 19 variables analyzed except in the SBP percentile, which is precisely a criterion included in the definition with four criteria.…”
Section: Discussionsupporting
confidence: 68%
“…Indeed, the area under the ROC curve for the HOMA criterion indicates that the probability of diagnosing a patient more accurately than a randomly chosen healthy child is just 85.4%, whereas for the IDF criteria this is only 65.9%. Consequently, when we considered the four diagnostic criteria, the proportion of children classified with MHO was similar to some studies carried out in adults (32), and the children classified with MHO had clinical and analytical variables similar to those who theoretically have MUO. No statistically significant differences were found in any of the 19 variables analyzed except in the SBP percentile, which is precisely a criterion included in the definition with four criteria.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, 102 full texts were carefully screened, and 39 more studies were removed because they were editorials or reviews and did not evaluate MHO/MUHO in children and/or adolescents. Accordingly, the scoping review included 63 studies 3,9,10,20–79 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Studies generally identified five groups of MHO definitions (Table 2): Group 1 ( n = 49; 77.8%) included zero risk factor, Group 2 ( n = 13; 20.6%) included ≤1 risk factor, Group 3 ( n = 3; 4.8%) included ≤2 risk factors, Group 4 ( n = 1; 1.6%) included ≤3 risk factors, and within Group 5 ( n = 1; 1.6%), data was defined based on quartile distributions. Some research have described more than one definition of MHO 3,9,23,28–30,32,52,56,61 . Estimates of MHO prevalence varied from 3% to 84.3% across the studies due to heterogeneity across various domains for defining the condition (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al in their study applied five different criteria of MHO in 4757 random adults to find the lowest prevalence of MHO (4.2%) when applying a criterion that included HOMA-IR (≤1.95) [7]. Also in adolescents, MHO prevalence decreases when IR is part of the criteria [24]. Khawaja et al in their study identified a definite disparity in cardiovascular risk between two groups of obese individuals-either with or without IR, along with a correspondingly unfavorable metabolic profile in the latter [25].…”
Section: Discussionmentioning
confidence: 99%